10. Isolation and Identification of Lactic Acid Bacteria Genus Pediococcus from Sumatran Orangutan (Pongo abelii) faeces at Kandi Zoo and Kinantan Zoo West Sumatera - Resti Reimena; Erina Erina; Darniati Darniati; Fakhrurrazi Fakhrurrazi; Darmawi Darmawi; Hamdani Budiman (Jurnal Medika Veterinaria, 2017)
This research has purposes to isolating and identifying the lactic acid bacteria genus Pediococcus in sumatran orangutan (Pongo abelii) feaces. Feaces are isolated from one orangutan at Kandi Zoo and two orangutans at Kinantan Zoo. The isolating of the lactic acid bacteria was done by using streak plate method with the MRSA (de Man Rogosa Sharpe Agar) specific media. Identification was done by the morphological observing, Gram stain, catalase test, oxidase test and biochemical test. The result showed that one isolate feaces from Kandi Zoo has cocci shaped with the isolate prediction approaches genus Pediococcus sp. The characteristic features of isolate are cocci shaped, Gram positive, tetrad cell structure, nonmotile, catalase negative, and oxidase negative. Based on these characteristics, it can be concluded that there is a lactic acid bacteria coloni which grouped into genus Pediococcus in male orangutan feaces from Kandi Zoo